Using Google Classroom in Enhancing Communicative Grammar Use and Attitudes of Non-English Specialized Post Graduates - Haggag, Haggag Mohamed (European Scientific Journal, ESJ, 2019)
This research integrates virtual language learning and the Communicative Language Teaching CLT approach for developing grammatical performance and attitudes towards English grammar use. It follows the one-group quasi-experimental design. Participants were randomly selected from the postgraduates General Diploma (41) at Hurghada Faculty of Education, Egypt. Instruments of the research included communicative grammar module through Google classroom application, communicative grammar test and a scale about the attitude towards English grammar use. It discussed how to design, instruct and assess a communicative grammar module by using Google Classroom virtual class. Results of the study showed a development in both the performance of participants’ use of English grammar as well as their positive attitudes towards grammar use. Following a one-group quasi-experimental design, the obtained results showed a development in participants’ grammar use (0.001) and also their positive attitudes (0.001) towards using grammar. Results also showed a strong correlation between the two variable; the coefficient scores were (0.779, 0.928 and 0.892) on Pearson, Kendall and Spearman coefficients respectively.